Developing an RME-based 3D storybook with AR technology to enhance spatial ability - Rochmat, Syaiful; Andriyani, Andriyani; Siswanto, Deny Hadi (Universitas Ahmad Dahlan, 2025)
This research aims to develop a 3D storybook using realistic mathematics education (RME) approach and augmented reality (AR) technology to enhance students' spatial ability. We used the ‘Analysis, Design, Development, Implementation, and Evaluation’ (ADDIE) development model and involved 34 eighth-grade students of SMP N 15 Yogyakarta – a public junior high school in Indonesia. During the development, we underwent several interviews, observations, asking experts’ validation to the content and the media, asking students’ response to the product, and tests related to the students' spatial ability. The results suggest that the content validation got an average score of 109 (good criteria), the media validation got an average score of 48.16 (good criteria), and the students response got an average score of 78.36 (very good criteria). At the end of the stage, there are still found an obstacle during the testing of the 3D storybook, namely the time required to load the 3D content. It makes some students encounter difficulty to access it, indicating the need for further development. However, the final product could facilitate the students to exercise their spatial ability using the 3D storybook while learning geometry.